2020
DOI: 10.1016/j.semcancer.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell approaches to cell competition: High-throughput imaging, machine learning and simulations

Abstract: Cell competition is a quality control mechanism in tissues that results in the elimination of less fit cells. Over the past decade, the phenomenon of cell competition has been identified in many physiological and pathological contexts, driven either by biochemical signaling or by mechanical forces within the tissue. In both cases, competition has generally been characterized based on the elimination of loser cells at the population level, but significantly less attention has been focused on determining how sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…When Δ HD was low or Λ was larger than 1, the change in competition outcome occurred because of a decrease in the local density of loser cells in mixed populations, which in turn led to decreased apoptosis. However, winners have an extra competitive edge because when free space becomes available due to cell death or cell area compressibility, they take advantage of the free space due to faster growth using a squeeze and take or a kill and take tactic [14]. At very long times, this effect alone may be sufficient for them to dominate in mixed populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When Δ HD was low or Λ was larger than 1, the change in competition outcome occurred because of a decrease in the local density of loser cells in mixed populations, which in turn led to decreased apoptosis. However, winners have an extra competitive edge because when free space becomes available due to cell death or cell area compressibility, they take advantage of the free space due to faster growth using a squeeze and take or a kill and take tactic [14]. At very long times, this effect alone may be sufficient for them to dominate in mixed populations.…”
Section: Resultsmentioning
confidence: 99%
“…One challenge in understanding cell competition from experimental data is that it takes place over several days, making the tracking of a cell’s environment and its eventual fate challenging. The emergence of automated long-term microscopy and advanced image analysis for segmentation and cell state recognition enables hypotheses to be formulated regarding the mechanisms of cell elimination [14]. For example, recent work has shown that loser cell death in an experimental model system for mechanical competition is strongly influenced by local cell density as expected, but that, in addition, division of winner cells appears favoured in neighbourhoods with many loser cells, something reminiscent of biochemical competition [15].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive evidence that environmental factors including stress, pollution and determinants of health all influence both acute and chronic inflammation, though in most instances the molecular mechanisms are not known or are incompletely understood. With the increasing accessibility of single cell biology ( Gradeci et al, 2020 ), in particular in immunophenotyping, there is accumulating evidence of the direct effects of even modest changes in acquired or environmental factors on integrated cellular responses.…”
Section: Evidence Of Environmental Selectionmentioning
confidence: 99%
“…To demonstrate the utility of this software, we employed PECAn to analyse parameters of ribosome protein mutant ( Rp/+ ) cell competition in Drosophila imaginal wing discs – a phenomenon whereby cells carrying heterozygous mutations in ribosomal protein genes, known as Minutes , are eliminated from mosaic tissues when proximal to wildtype cells 7 (Supplementary Figure 1). Rp/+ cells are therefore said to act as ‘losers’ relative to wildtype ‘winners.’ In the field of cell competition, in particular, there is a pressing need for automated image and single cell analytic techniques 8 . The use of PECAn allowed us to: identify an unappreciated sexual dimorphism in Rp/+ cell competition, characterize rigorously Rp/+ cell death properties in competing and non-competing tissues, and identify by logistic regression analysis the tissue parameters that accurately model and predict competitive cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Rp/+ cells are therefore said to act as 'losers' relative to wildtype 'winners.' In the field of cell competition, in particular, there is a pressing need for automated image and single cell analytic techniques 8 . The use of PECAn allowed us to: identify an unappreciated sexual dimorphism in Rp/+ cell competition, characterize rigorously Rp/+ cell death properties in competing and noncompeting tissues, and identify by logistic regression analysis the tissue parameters that accurately model and predict competitive cell death.…”
Section: Introductionmentioning
confidence: 99%